An introduction to Jewish law / François-Xavier Licari. - Licari, François-Xavier (Cambridge University Press, 2019)
Jewish law is a singular legal system that has been evolving for generations. Often conflated with Biblical law or Israeli law, Jewish law needs to be studied in its own right. An Introduction to Jewish Law expounds the general structure of Jewish law and presents the cardinal principles of this religious legal system. An introduction to modern Jewish law as it applies to the daily life of Jews around the world, this volume presents Jewish law in a way that answers all the questions that a student of comparative law would ask when encountering an unfamiliar legal system. Sources of Jewish law such as revelation, rabbinical and communal legislation, judicial decisions, and legal reasoning are defined and analyzed, and the authority of who decides what Jewish law is and why their decisions are binding is investigated.